PENGARUH LEVERAGE, STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS - Hesti Setiorini; Amelia Nur Anggraini; Ahmad Sumarlan; Rina Yuniarti (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the effect of leverage, capital structure, and company growth on financial distress in basic materials companies listed on the Indonesia Stock Exchange. The research method used is a quantitative method with secondary data in the form of annual financial reports for the period 2021–2023 obtained from the Indonesia Stock Exchange. The research sample was determined using a purposive sampling technique, resulting in 135 observational data. Data analysis was performed using multiple linear regression accompanied by classical assumption tests, partial tests (t-tests), simultaneous tests (F-tests), and coefficient of determination tests. The results show that leverage has a positive and significant effect on financial distress, while capital structure and company growth have no significant effect on financial distress. Simultaneously, leverage, capital structure, and company growth have a significant effect on financial distress. The conclusion of this study indicates that the higher the level of company leverage, the greater the risk of financial distress, while capital structure and company growth are not able to explain the condition of financial distress individually in basic materials companies. Keywords: Leverage, Capital Structure, Corporate Growth, Financial Distress, Basic Materials